Criminalizing the Care Work Zone? The Gendered Dynamics of Using Legal and Administrative Strategies to Confront Workplace Violence - Baines, Donna (Social justice, 2005)
Part of a special issue on the many faces of violence. The writer asserts that, in light of the restructured gendered, caring, and paternalistic context in which violence occurs, legal and administrative solutions are not likely to yield more than minor success in preventing workplace violence in the care work zone. She analyzes four key administrative and criminal law remedies—the right to refuse dangerous work, the duty to warn, assault charges, and criminalizing employer neglect—and considers their prospects for addressing violence within the specific, gendered context of care work and with a workforce that is poorly protected from management retaliation and from their own concerns for marginal and vulnerable clients.